2004
DOI: 10.1021/cc0340731
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Synthesis of Substituted Biaryls and Heterocyclic Arylamines

Abstract: In this paper, we report very general conditions that enable palladium-mediated coupling reactions on the solid support. A wide variety of biaryls and arylamines (including pyrimidines) have been synthesized using this protocol. The chemistry facilitates a combinatorial approach to the production of large numbers of medicinally relevant heterocyclic structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…13 C NMR (CDCl 3 , 75 MHz), δ (ppm): 171.5, 161.4, 150.9, 150.7, 68.1, 51.9, 44.4, 32.7. MS (70 eV) m/z (%): 324 (M + , 21), 264 (7), 238 (6), 208 (11), 127 (59), 59 (100). HRMS (EI): C 8 H 9 -IN 2 O 4 calcd, 323.9607; found, 323.9612.…”
Section: -(5-iodo-24-dioxo-34-dihydro-2h-pyrimidin-1-yl)propionic Aci...mentioning
confidence: 99%
See 1 more Smart Citation
“…13 C NMR (CDCl 3 , 75 MHz), δ (ppm): 171.5, 161.4, 150.9, 150.7, 68.1, 51.9, 44.4, 32.7. MS (70 eV) m/z (%): 324 (M + , 21), 264 (7), 238 (6), 208 (11), 127 (59), 59 (100). HRMS (EI): C 8 H 9 -IN 2 O 4 calcd, 323.9607; found, 323.9612.…”
Section: -(5-iodo-24-dioxo-34-dihydro-2h-pyrimidin-1-yl)propionic Aci...mentioning
confidence: 99%
“…One of the most promising strategies in this field is the use of transition-metal-catalyzed reactions, which provide powerful tools for creating molecular diversity matching the space of biological targets with relevant chemistry. However, despite their enormous potential, examples of such transformations in library production are still rare, and there is, therefore, a dearth of new methodologies that are able to deliver large heterocyclic-based libraries. With the exception of the above-cited newer strategies and some elegant examples, one-pot synthesis of heterocyclic libraries is still generally dominated by the use of classical heteroannulation approaches, which provide collections of moderate functional diversity and limited scaffold variability.…”
mentioning
confidence: 99%
“…Another method is the introduction of trioctylphosphineoxide (TOPO) into the coupling reaction, which allows solubilization of Pd metal as a colloid [84] and results in the formation of precipitates of larger particle size, effectively filterable through a P5 frit. Ma et al [85] reported a method to remove most dark-colored impurities from StratoSpheres PL-FDMP resin. Here, the resin was treated with equal volumes of THF/H 2 O 50:1 (v/v) and 1 m LiBF 4 in MeCN and then agitated for 1 h. Recently, Iwasawa et al presented novel pyridine ligands having 2,3,4,5-tetraphenylphenyl moieties, which efficiently suppress Pd black formation in Pd-mediated oxidation of alcohols; however, the use of these catalyst systems for aryl-aryl coupling has not yet been reported [86].…”
mentioning
confidence: 99%